2021
DOI: 10.1002/jgh3.12548
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of fecal calprotectin in predicting significant gastrointestinal diseases

Abstract: Background and Aim: It is often unreliable to triage patients for timely endoscopic investigations based on symptoms alone. We need an objective assessment to differentiate between organic gastrointestinal diseases and functional bowel symptoms. We evaluated the diagnostic accuracy of fecal calprotectin (FC) in predicting organic gastrointestinal diseases. Methods: In a prospective observational study, consecutive patients referred for colonoscopy to the Department of Medicine and Geriatrics at the Kwong Wah H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 37 publications
(27 reference statements)
0
11
0
1
Order By: Relevance
“…La sensibilidad y la especificidad del nivel elevado de calprotectina fecal para los hallazgos significativos de la colonoscopia fueron 100 y 44.4%, respectivamente. Es decir, 100% de los pacientes con dolor abdominal tuvieron CF positiva, en contraparte nuestro estudio encontró solo el 48.57%, esto posiblemente al grupo mayor de población estudiada en el nuestro (Kan et al, 2021). Para esta investigación, se demostró que pacientes con niveles elevados de CF y sin patología endoscópica fueron el 13.2%.…”
Section: Discussionunclassified
“…La sensibilidad y la especificidad del nivel elevado de calprotectina fecal para los hallazgos significativos de la colonoscopia fueron 100 y 44.4%, respectivamente. Es decir, 100% de los pacientes con dolor abdominal tuvieron CF positiva, en contraparte nuestro estudio encontró solo el 48.57%, esto posiblemente al grupo mayor de población estudiada en el nuestro (Kan et al, 2021). Para esta investigación, se demostró que pacientes con niveles elevados de CF y sin patología endoscópica fueron el 13.2%.…”
Section: Discussionunclassified
“…9,10 However, elevated FC has been ascribed to several other factors, including treatment with nonsteroidal antiinflammatory drugs (NSAIDs), proton pump inhibitors (PPIs), or acetylsalicylic acid (ASA). 6,[11][12][13] Previous studies have confirmed elevated FC in 32-57% of the patients with normal colonoscopy 11,14,15 and found an association with these drugs. 11 The measures of FC test accuracy have mainly been performed in selected secondary care populations, and the evidence available from primary care is still limited.…”
Section: Introductionmentioning
confidence: 87%
“…However, elevated FC has been ascribed to several other factors, including treatment with nonsteroidal anti‐inflammatory drugs (NSAIDs), proton pump inhibitors (PPIs), or acetylsalicylic acid (ASA) 6,11–13 . Previous studies have confirmed elevated FC in 32–57% of the patients with normal colonoscopy 11,14,15 and found an association with these drugs 11 …”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils play a major role in the release of calprotectin at sites of inflammation, and faecal calprotectin (FC) has long been considered a potential biomarker of colorectal polyps and cancer [ 33 ]. However, FC is shown to have limited diagnostic accuracy for identifying patients with CRC, irrespective of stage [ 33 , 34 , 35 , 36 , 37 ] and this is reinforced by studies that have compared the sensitivity and specificity of FC to quantitative FIT in this setting [ 21 , 23 , 30 , 38 , 39 ].…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…The benefit of measuring FC levels in stool samples of patients who present in primary care with symptoms may instead be linked to the negative predictive value (NPV) of the test in a CRC diagnostic setting. Studies to date report NPV between 97.2–98.7 for CRC, and 93.2–97.2 for high-risk adenomas [ 21 , 37 , 39 , 40 ]. NICE guidelines accept a 3% risk in missing CRC in setting symptom criteria for referral [ 41 ], leading to the suggestion that FC concentrations below an established threshold may help rule out younger patients who more commonly present with nonspecific lower GI symptoms [ 42 ].…”
Section: Inflammatory Markersmentioning
confidence: 99%